Analisa Kinerja Penjualan Berdasarkan Rasio Ekonomi, Efiseinsi Dan Efektifitas Pada PT Mega Prabu Mandiri Prabumulih - Kumala iskandari, Ghovinda; Herlin; Astuti, Kamelia (Jurnal Ilmiah Raflesia Akuntansi, 2025)
The study aims to analyze the sales performance of PT Mega Prabu Mandiri based on three main indicators, namely economic ratio, efficiency, and effectiveness, during 2023 to 2024. The method used in this study is a descriptive quantitative approach with secondary data in the form of budget reports and the realization of company income and expenses. The results of the study indicate that the company's economic ratio in 2023 was 122% and increased to 133% in 2024. This value indicates that expenditures exceeded the budget, so the company was not operating economically. Meanwhile, the efficiency ratio decreased from 85% in 2023 to 83% in 2024, indicating an increase in efficiency in the use of operational costs. The effectiveness ratio was recorded at 124% in 2023 and increased to 126% in 2024, indicating that the company successfully exceeded its predetermined sales targets.